2021
DOI: 10.7150/ijms.54460
|View full text |Cite
|
Sign up to set email alerts
|

Screening, identification and interaction analysis of key MicroRNAs and genes in Asthenozoospermia

Abstract: Background: Asthenozoospermia, one of the most common causes of male infertility, is a complicate multifactorial pathological condition that genetic factors are involved in. However, the epigenetic signature and mechanism of asthenozoospermia still remain limited. Our study aimed to confirm the key microRNAs (miRNAs) and genes in asthenozoospermia and demonstrate the underlying epigenetic regulatory mechanisms. Methods: We screened out and pooled previous studies to extracted… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Another similar study with 39 men having unexplained asthenozoospermia was conducted, and the authors found that the expression level of miR‐888‐3p increased significantly in patients with unexplained asthenozoospermia (Heidary et al, 2019). As shown in Table 3, the expression level of miR‐374b was lower in asthenozoospermic cases than infertile men, making it a potential non‐invasive biomarker to predict asthenozoospermia (Li & Chen, 2021). In a recent article, semen samples were collected from a total of 71 infertile men, and a reduction in the expression of miR‐510‐ 5p was reported in the semen samples of patients with teratozoospermia and asthenozoospermia in comparison with case–control (normozoospermia and teratoasthenozoospermia) (Hasheminiya et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Another similar study with 39 men having unexplained asthenozoospermia was conducted, and the authors found that the expression level of miR‐888‐3p increased significantly in patients with unexplained asthenozoospermia (Heidary et al, 2019). As shown in Table 3, the expression level of miR‐374b was lower in asthenozoospermic cases than infertile men, making it a potential non‐invasive biomarker to predict asthenozoospermia (Li & Chen, 2021). In a recent article, semen samples were collected from a total of 71 infertile men, and a reduction in the expression of miR‐510‐ 5p was reported in the semen samples of patients with teratozoospermia and asthenozoospermia in comparison with case–control (normozoospermia and teratoasthenozoospermia) (Hasheminiya et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In our study, two asthenozoospermia datasets were selected from the GEO database based on previous literature reports, and these data proved to be reliable[ 13 , 15 ]. Two asthenozoospermia GSE profiles include GSE92578 (GPL20301 Illumina HiSeq 4000 [Homo sapiens]), containing 3 asthenozoospermia sample and 4 normal sample[ 9 ], and GSE22331 (GPL570 [HG-U133_Plus_2] Affymetrix Human Genome U133 Plus 2.0 Array), containing one asthenozoospermia and normal sample[ 12 ].…”
Section: Data Collectionmentioning
confidence: 99%
“…Abnormalities at the genomic level, including genes and signaling pathways related to this disease, have increasingly been identified between fertile men and patients with asthenozoospermia [8][9][10][11][12]. The large amount of gene sequencing data available has provided a convenient resource for analyzing the regulation of gene expression in asthenozoospermia using increasingly complex analytical techniques [13]. In the current manuscript, we obtained differentially expressed genes (DEGs) in patients with asthenozoospermia using the GSE92578 and GSE22331 datasets from the Gene Expression Omnibus (GEO) database.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that asthenozoospermia is due to energy deficiency and structural abnormalities of sperm ( du Plessis et al, 2015 ; Sironen et al, 2020 ). Numerous reasons may contribute to asthenozoospermia, such as varicocele ( Zhu et al, 2018 ), oxidative stress ( Nowicka-Bauer et al, 2018 ), genetic factors ( Li and Chen, 2021 ), environmental pollutants ( Benoff et al, 2008 ), nutrition ( Moghadam et al, 2020 ), and lifestyle ( Gaur et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%